Respostas

2014-06-28T15:19:07-03:00
Olá
x² - 4x + 1 = 0
Δ = b² - 4.a.c 
Δ = -4² - 4 . 1 . 1 
Δ = 16 - 4. 1 . 1 
Δ = 12

m = (-b +- √Δ)/2a
m' = (--4 + √12)/2.1                   n'' = (--4 - √12)/2.1
m' = 4+2
√3 / 2                          n'' = (4-2√3) / 2
m' = 2+
√3                                 n'' = 2-√3

então (m + 7) (n + 7)
          (2+√3 +7)  (2-√3 +7)= (9+√3)(9-√3) = 81-9√3 +9√3 - (√3)2  = 81-3 = 78
7 4 7
Obrigada mesmo. Tenho outra pergunta de matemática, você poderia dar uma olhada? http://brainly.com.br/tarefa/741864
2014-06-28T16:05:31-03:00
 x² - 4x + 1 = 0, p/ a = 1, b = -4 e c = 1
Δ = (-4)² - 4(1)(1) = 16-4 = 12
m = (4+√12)/2
n = (4-√12)/2
(m+7)(n+7) = [(4+√12)/2 + 7][(4+√12)/2 - 7] = (4+√12 + 14)/2.(4-√12+14)/2 = 
= (18+√12)/2. (18-√12)2 = 
= (9 +√12/2)(9-√12/2) = 
= (9)² - (√12/2)² = 
= 81 - (12/4) = 81 - 3 = 78 ====>>> LETRA B
2 5 2